Higher induction and maintenance infliximab trough levels are associated with radiological perianal fistula healing in pediatric patients with Crohn's disease - Son, Joonhyuk; Park, Sungjoo; Kim, Seon Young; Kim, Yoon Zi; Kim, Hansol; Kim, Wontae; Lee, Sanghoon; Seo, Jeong-Meen; Choe, Yon Ho; Kim, Mi Jin (Frontiers in Pediatrics, 2025)
BackgroundLiterature on the association between high infliximab (IFX) trough levels and perianal fistula response in pediatric patients with perianal fistulizing Crohn's disease (PFCD) is limited. This study aimed to evaluate the association between IFX trough levels and radiological perianal fistula healing in pediatric patients with PFCD undergoing long-term IFX treatment.MethodsThe study included pediatric patients (aged <18 years) diagnosed with PFCD who received IFX treatment and underwent follow-up magnetic resonance imaging (MRI) at 1 year. The primary outcome was radiological fistula healing on MRI one year after IFX treatment.ResultsA total of 82 patients were included and 57 (69.5%) achieved radiological fistula healing at the 1-year follow-up. Patients with radiological fistula healing had lower rates of reoperation (p = 0.021), and higher median IFX trough levels at week 2 (median, 17.6 vs. 14.1 μg/ml), week 6 (11.79 vs. 7.11 μg/ml), week 30 (3.9 vs. 1.1 μg/ml), and week 54 (7.6 vs. 3.7 μg/ml) (p = 0.043, 0.003, 0.007 and <0.001, respectively) compared to those who had no fistula healing. In the multivariate analysis, higher median IFX trough levels at week 6 and week 54 remained significant factors associated with radiological fistula healing (p = 0.039 and 0.018, respectively). Optimal cut-off IFX trough levels for radiological fistula healing showing the highest area under curve (AUC) score was 9.7 μg/ml [AUC: 0.792, 95% confidence interval (CI): 0.630–0.955; p = 0.005] for week 6, and 5.1 μg/ml (AUC, 0.848; 95% CI: 0.750–0.947; p < 0.001) for week 54.ConclusionThere was a significant association between higher serum IFX trough levels (during induction and maintenance) and radiological perianal fistula healing after 1 year of IFX treatment in pediatric patients with PFCD.